Burnout among disability activists in England: Insights from the Oldenburg Burnout Inventory - Lyla Adwan-Kamara; Fabrício M. Fialho; Amanpreet Ahluwalia; Husnara Zaman; Michelle Daley; Peter Beresford OBE (PLoS ONE, 2026)
Objectives To contribute to the understanding of burnout among Disabled activists in the disability movement - ‘disability activists’ - in England using the Oldenburg Burnout Inventory, and provide insights into the prevalence and features of burnout among this group. Methods The self-completed online survey collected data on burnout among adults who self-identify as Disabled and as activists in the disability movement. The survey used questions on activism, socio-demographics, the Oldenburg Burnout Inventory for burnout assessment, and other attitudinal questions. The sample included 134 respondents recruited through disability-related organisations and disability-related activist networks. An important aspect of the method was oversight by a steering group of lived experience disability experts, and to prioritise survey accessibility. Results A varied spectrum of impairment types was selected by respondents with the majority of respondents reporting long-term health conditions, and 74% reported having more than one impairment. Eighty-eight per cent of respondents reported that they undertake unpaid activism and 64% were undertaking paid activism. The Oldenburg Burnout Inventory has two dimensions – disengagement and exhaustion – which are strongly correlated ( ϕ = 0.83), however, respondents differ significantly in their burnout levels in each dimension and tend to be significantly more exhausted than disengaged. Bivariate analysis shows that impairment type and lived experiences impact on the experience of burnout in ways that most of the other socio-demographic categories do not, respondents with energy-limiting conditions were particularly burnt out. Age and place of activism also make a difference in the experience of burnout, with younger disability activists and activists in charities not run by Disabled People having higher levels of burnout. Respondents self-assessed their level of burnout and results were closely correlated with the Oldenburg Burnout Inventory, suggesting that respondents understand whether they are burnt out and the intensity of their burnout. They also identified the key drivers of burnout which wasn’t their activism but rather the barriers that they face when confronted with ableism and the impact that ableist systems of oppression have on them. Conclusions The survey findings raise a number of important points adding to our understanding of burnout among disability activists. Some respondents mentioned support from and solidarity with others as a protective factor from burnout, which should be further explored.